Multilateral Debt Relief through the Eyes of Financial Markets - Raddatz, Claudio (2012)
The economic benefits of debt relief for recipient countries have been the subject of arduous debate, at least partly motivated by the difficulty of identifying the causal effect of debt relief on economic performance-given that performance itself may drive the decision to grant relief. This paper conducts an event study to assess the economic consequences of multilateral debt relief for recipient countries that is robust to these reverse causality issues. It estimates the response of the stock prices of South African multinationals with subsidiaries in those countries to the announcement of debt relief initiatives, and shows that stock prices exhibit a significant increase above those of other firms, especially around the launching of the recent Multilateral Debt Relief Initiative. The improvement in financial markets' assessment of the value of these multinationals is consistent with lower expected levels of future taxation in the recipient countries. Overall, the results are consistent with the "debt overhang" argument for debt relief.